Genomic analysis reveals high intra-species diversity of Shewanella algae. Issue 2 (10th February 2022) - Huang, Zhenzhou; Yu, Keyi; Fu, Songzhe; Xiao, Yue; Wei, Qiang; Wang, Duochun
Abstract : Shewanella algae is widely distributed in marine and freshwater habitats, and has been proved to be an emerging marine zoonotic and human pathogen. However, the genomic characteristics and pathogenicity of Shewanella algae are unclear. Here, the whole-genome features of 55 S . algae strains isolated from different sources were described. Pan-genome analysis yielded 2863 (19.4 %) genes shared among all strains. Functional annotation of the core genome showed that the main functions are focused on basic lifestyle such as metabolism and energy production. Meanwhile, the phylogenetic tree of the single nucleotide polymorphisms (SNPs) of core genome divided the 55 strains into three clades, with the majority of strains from China falling into the first two clades. As for the accessory genome, 167 genomic islands (GIs) and 65 phage-related elements were detected. The CRISPR-Cas system with a high degree of confidence was predicted in 23 strains. The GIs carried a suite of virulence genes and mobile genetic elements, while prophages contained several transposases and integrases. Horizontal genes transfer based on homology analysis indicated that these GIs and prophages were parts of major drivers for the evolution and the environmental adaptation of S. algae . In addition, a rich putative virulence-associated gene pool was found. Eight classes of antibiotic-associated resistance genes were detected, and the carriage rate of β-lactam resistance genes was 100 %. In conclusion, S. algae exhibits a high intra-species diversity in the aspects of population structure, virulence-associated genes and potential drug resistance, which is helpful for its evolution in pathogenesis and environmental adaptability.